The Use of the Wordwall Application as a Game-Based Learning Media to Overcome Multiplication Learning Difficulties in IV Students of Muhammadiyah Elementary School - Riska Hartanti; Markhamah Markhamah; Ambarwati Ambarwati (Journal of Educational Sciences, 2026)
Many elementary school students, especially fourth graders, still experience difficulties in understanding the concept of multiplication. This is influenced by the use of conventional learning methods that tend to be less interesting, thus reducing learning motivation and causing students to be less active in the mathematics learning process. This study aims to describe the difficulties in learning multiplication and the implementation of game-based learning media using the Wordwall application in improving student understanding. The research method uses a descriptive qualitative approach with subjects of fourth grade students of Muhammadiyah Elementary School Tanjungpinang in the 2024/2025 academic year. Data collection techniques include observation, interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results of the study show that Wordwall is able to increase students' enthusiasm, activeness, and understanding in multiplication through fun interactive exercises. Thus, Wordwall is an effective alternative learning media to overcome difficulties in learning multiplication in elementary school students.